Direct bandgap narrowing in Ge LED's on Si substrates - Oehme, Michael; Gollhofer, Martin; Widmann, Daniel; Schmid, Marc; Kaschel, Mathias; Kasper, Erich; Schulze, Jörg (Optics Express, 2013)
In this paper we investigate the influence of n-type doping in Ge light emitting diodes on Si substrates on the room temperature emission spectrum. The layer structures are grown with a special low temperature molecular beam epitaxy process resulting in a slight tensile strain of 0.13%. The Ge LED's show a dominant direct bandgap emission with shrinking bandgap at the Γ point in dependence of n-type doping level. The emission shift (38 meV at 1020 cm-3) is mainly assigned to bandgap narrowing at high doping. The electroluminescence intensity increases with doping concentrations up to 3×1019 cm-3 and decreases sharply at higher doping levels. The integrated direct gap emission intensity increases superlinear with electrical current density. Power exponents vary from about 2 at low doping densities up to 3.6 at 1020 cm-3 doping density. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-29